Morphological and Molecular Identification of Fusarium oxysporum Sch. Isolated From Guava Wilt in Bangladesh - Hussain, M Zakir; Rahman, MA; Islam, Mohammad Nurul; Latif, MA; Bashar, MA (Bangladesh Journal of Botany, 2012)
Wilt of guava plants (Psidium guajava L.) is a serious disease in Bangladesh. Sixteen isolates of Fusarium oxysporum Sch. were collected from the root and stem fragments of guava plants growing in six districts of Bangladesh. Species identity was based on the colony character, nature of conidiogenous cell, morphology of microconidia, macroconidia and chlamydospores. Eleven isolates were confirmed as F. oxysporum through polymerase chain reaction (PCR) using species specific primers designed from the conserved regions of 18S rRNA gene. DOI: http://dx.doi.org/10.3329/bjb.v41i1.11082 Bangladesh J. Bot. 41(1): 49-54, 2012 (June)